Packet size adjustment for minimizing the average delay in buffer-aided cognitive machine-to-machine networks. (May 2018) - Darabi, Mostafa; Montazeri, Ali Mohammad; Maham, Behrouz; Saad, Walid; Zarrabi, Houman
Abstract: In this paper, a cognitive machine-to-machine (CM2M) network is considered in which underlaid on a macro cell, there exist some co-existing small cell based M2M networks. In each small cell, M2M network is comprised of some machine type devices (MTDs) and an MTD gateway. The MTD gateway collects data of MTDs within each small cell and transmits it to the small cell base station reusing the spectrum of the macro cell. To avoid data loss, MTD gateway is equipped with a buffer. In the considered CM2M network, MTDs with delay sensitive application are prioritized over MTDs having delay tolerant packets. In order to minimize the average delay of the MTDs, a novel packet adjustment scheme is proposed. The average delay and the average throughput of the CM2M network are computed. Simulation results show that the proposed scheme outperforms conventional policy without packet adjustment in terms of average delay of MTDs.